Comprehension and production strategies for academic texts at university. (UNIHumanitas, 2013)
This descriptive research is about perception and cognitive and metacognitive strategies of comprehension and production of academic texts, and an approach to the teacher as a mediator of these strategies in higher education. Hence, its purpose was to investigate the perception of teachers and university students regarding the comprehension and production of academic texts and the learning strategies that these teachers propose in order to achieve the development of both skills.
Keywords: cognitive strategies; metacognitive strategies; reading and writing; academic texts